Growth of n-ZnOnanorods on p-GaN using an Aqueous Solution Method - Mohammad, Sabah M.; Hassan, Z.; Ahmed, Naser M. (2015)
Wide band gap semiconductors like GaN and ZnO have high electron mobility and wide band gap energy. Zinc oxide (ZnO)nanorod arrays are grown on a seed-layer ZnO/GaN l sapphire substrate using a wet chemical bath deposition method. Chemical solution deposition is a low-temperature and possibly the lowest-cost method of growing ZnOnanorods on a GaN substrate. Field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) measurements were used to examine the morphology, phase growth orientation and the structure of the ZnOnanorods and the GaN thin film. Optical property of the as-grown ZnOnanorodsand the GaN thin film was analyzed by room temperature photoluminescence measurements. The synthesis of vertically well-aligned nZnOnanorods on p-GaN film with large aspect ratio, high optical quality, and high density can be very useful for fabricating nanoelectronic and nano-optical devices.